ANALYSIS PERFORMANCE SYSTEM LEARNING BASED ON GAMES FOR STUDENTS OF EDUCATIONAL TECHNOLOGY STUDY PROGRAM - Hasni, Hasni; Sampelolo, Rigel (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This study examines the performance analysis of game-based learning systems. The qualitative research method with a qualitative descriptive approach allows researchers to explore in-depth understanding and explain the meaning of the phenomena studied, especially in the context of performance game-based learning. By collecting data through a questionnaire, this study evaluates students' perceptions of game-based learning systems. The study results showed that the average flat student responds positively to game-based system learning. This has been proven to increase students' interest, motivation, understanding, and skills. Thus, it is essential to consider its potential negative impacts and implement them responsibly and effectively through system, learning, and implementation games.